2019
DOI: 10.3389/fmicb.2019.00872
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biogenic Amines and Microbial Contribution in Traditional Chinese Sausages

Abstract: Biogenic amines (BAs) in sausages represent a health risk for consumers, and thus investigating the BAs accumulation mechanism is important to control the BAs. In this study, the BAs profiles of 16 typical Chinese sausage samples were evaluated, and 8 kinds of common BAs were detected from different samples. As a whole, the BAs contents of the majority of Chinese sausage samples were within the safe dosage range, except that the total BAs and histamine concentrations of sample HBBD were above the toxic dosage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 57 publications
(70 reference statements)
0
24
0
Order By: Relevance
“…In recent years, there are some studies related to the impact of microbial diversity on BAs formation in fermented food, such as fish sauce, sausages, and soy sauce (Li et al, 2018(Li et al, , 2019Wang et al, 2018). While shrimp paste from different manufacturers at home and abroad have been used as raw materials to study their biochemical, nutritional, sensory characteristics, and to findings from such studies have been used to screen for starter cultures (Cai et al, 2017;Pongsetkul et al, 2017;Kim et al, 2019), there has been no research investigating the production of BAs in grasshopper sub shrimp paste, and the connection between BA production and the quality of the paste.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there are some studies related to the impact of microbial diversity on BAs formation in fermented food, such as fish sauce, sausages, and soy sauce (Li et al, 2018(Li et al, , 2019Wang et al, 2018). While shrimp paste from different manufacturers at home and abroad have been used as raw materials to study their biochemical, nutritional, sensory characteristics, and to findings from such studies have been used to screen for starter cultures (Cai et al, 2017;Pongsetkul et al, 2017;Kim et al, 2019), there has been no research investigating the production of BAs in grasshopper sub shrimp paste, and the connection between BA production and the quality of the paste.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous researches, the corresponding SAM transporters have been identified in E. coli, Streptomyces coelicolor etc., (Lee et al, 2012;Yang et al, 2014;Husna et al, 2018), also, the intracellular SAM concentration at 30 h was increased by 53.69% after SAM addition, suggested that additional SAM could be imported by amino acid transporter, thus, we suggested that SAM transporter is also present in B. licheniformis DW2, although it has not been identified or annotated. In addition, SAM decarboxylase gene speD was deleted to block synthetic pathway of byproduct, meantime, based on our results, two other harmful by-products, cadaverine and putrescine (Li et al, 2019), were also decreased by 27.50 and 37.04%, due to the weakening of amino acid decarboxylase ( Figure 6C), and this result was positively correlated with our previous research (Wu et al, 2019). Furthermore, since SAM synthetase catalyzed the formation of SAM from Met and ATP, as well as the critical role of ATP supply in physiological metabolism (Cai et al, 2018), the ATP pool of DW2-KENPND should be enhanced in our future work.…”
Section: Discussionmentioning
confidence: 80%
“…[17,29]. Some genera detected throughout the fermentation process, such as Staphylococcus, also played an important role in the quality and safety of fish sauce products, which is often used as a starter in fermented foods and can be used to control BAs during food fermentation [30].…”
Section: Discussionmentioning
confidence: 99%